2013
DOI: 10.1016/j.bbr.2012.07.021
|View full text |Cite
|
Sign up to set email alerts
|

The BTBR T+tf/J mouse model for autism spectrum disorders–in search of biomarkers

Abstract: Autism spectrum disorders (ASD) form a common group of neurodevelopmental disorders appearing to be under polygenic control, but also strongly influenced by multiple environmental factors. The brain mechanisms responsible for ASD are not understood and animal models paralleling related emotional and cognitive impairments may prove helpful in unraveling them. BTBR T+tf/J (BTBR) mice display behaviors consistent with the three diagnostic categories for ASD. They show impaired social interaction and communication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
94
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(105 citation statements)
references
References 118 publications
4
94
1
2
Order By: Relevance
“…4e). These findings strongly support previous studies that suggested a social behaviour deficiency in the BTBR mouse strain 29,31 . Moreover, we found that by using four social behaviour features collected by the system in a single testing day, we could predict the mouse strain with an accuracy of about 90-95% (see Methods and Supplementary Fig.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…4e). These findings strongly support previous studies that suggested a social behaviour deficiency in the BTBR mouse strain 29,31 . Moreover, we found that by using four social behaviour features collected by the system in a single testing day, we could predict the mouse strain with an accuracy of about 90-95% (see Methods and Supplementary Fig.…”
Section: Resultssupporting
confidence: 92%
“…The integrated video-RFID system was applied to test two inbred mouse strains: C57BL/6 Â 129Sv (C57 Â 129) and BTBR T þ tf/J (BTBR), which were previously reported to exhibit significantly different behavioural phenotypes [29][30][31] . Three independent groups of mice were tested for each of the mouse strains (that is, a total of six experiments), using an identical standard operation protocol; the duration of each experiment was 8 days.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The complex phenotypes of autism are difficult to model in mice (Moy et al, 2006;Patterson, 2011;Silverman et al, 2010b), thereby slowing the development of successful therapies. Nonetheless, the three diagnostic criteria of autism (eg, impaired sociability, abnormal communication, and excessive stereotypic behaviors) are expressed by the BTBR T þ Itpr3 tf /J (formerly BTBR T þ tf/J and hereafter 'BTBR') inbred strain (McFarlane et al, 2008;Meyza et al, 2013;Scattoni et al, 2011). These findings indicate that the BTBR strain might be a useful model for aspects of idiopathic (polygenetic) autism.…”
Section: Introductionmentioning
confidence: 99%
“…Further, these types of mice have been analyzed using various behavioral tests including an elevated plus maze, a mouse defense battery, an elevated zero-maze, a three-chambered social approach test, etc. (Bolivar et al, 2007;Meyza et al, 2013;Moy et al, 2007;Pobbe et al, 2011;Silverman et al, 2010;Wohr et al, 2011). Since numerous immune abnormalities have been reported in autism (Ashwood & van de Water, 2004;Stigler et al, 2009), the current study investigated the immune system of BTBR mice.…”
Section: Discussionmentioning
confidence: 99%